الأزمات المترتبة عن تطبيق المحاصصة السياسية الطائفية في لبنان (1990 – 2023م) (Economic studies journal, 2023)
The study dealt with the issue of political sectarianism and the resulting crises within the Lebanese state, through two requirements. The first dealt with the historical roots of sectarianism in Lebanon and its demographic and political divisions, and the stages it went through from the Ottoman Empire until the date of this study. It also dealt with the demographics and the nature of the Lebanese political system and party life.     As for the second requirement of the study, it dealt with the crises that resulted from the implementation of the sectarian system in Lebanon, such as the security crisis represented by the spread of assassination crimes, security chaos and the proliferation of weapons, and the economic and financial crisis represented by administrative and financial corruption and the collapse of the value of the Lebanese currency, the crisis of identity and citizenship, and the crisis of reforming the political system. sectarianism, and the crisis of foreign interventions.The study concluded that the tragic situation that Lebanon is witnessing is caused by the adoption of sectarianism as the basis for the system of government in the country.
Keywords: Sectarian quotas; the Lebanese civil war; consensual democracy; Taif Accord; Lebanese parties; corruption; foreign interference